92 Enhanced early-life nutrition promotes reproductive and metabolic organ development in heifer calves. (7th December 2018) - Kelly, A; Byrne, C; Kenny, D; Lonergan, P
Abstract: Early-life nutrition is reported to increase reproductive performance in cattle. The aim of this study was to examine the effect of enhanced nutrition during the first 21 weeks of life on reproductive and metabolic organ growth in heifers. Holstein-FriesianXAngus heifer calves with a mean (±S.D.) age and bodyweight of 19(±5) days and 51.2(±7.8) kg, respectively, were assigned to either a high-energy diet (HE;n = 16; targeted ADG 1.2kg/d) or a control diet (CONT;n = 16; targeted ADG 0.50kg/d). At 145 ± 3 days of age, calves were euthanized and the reproductive tract was excised, dissected (into uterus, cervix and ovary) and weighed together with the anterior-pituitary, liver, heart, lungs, and gastrointestinal tract (GIT). Calves on the HE diet were 189.6kg and CONT diet were 110.2kg, resulting in a 78.4kg weight differential (P < 0.001) at slaughter between the treatment groups. Calves on HE growth was 1.18kg/day and their contemporizes on the CONT achieved 0.502kg/day (P < 0.001). Calves offered the HE diet had greater (P < 0.001) total reproductive tract weight, along with cervix, uterus and ovarian tissue compared CONT calves. Total reproductive tract, cervix, uterus and ovarian tissue when expressed on a body weight basis remained different (P < 0.001) between dietary treatments. Metabolic organs viz heart, lungs, liver, GIT along with the anterior pituitary were greater for calves offered the HE diet (P < 0.001). Early life growth was positively associated (P < 0.001) with reproductive tract, uterus, and ovarian tissue, along with liver and anterior pituitary weight. Indeed, size of anterior pituitary, the liver and the ovary were all positively related to one another (P < 0.05) on an absolute or bodyweight basis.. In conclusion, enhanced early-life nutrition can increase the size of the reproductive tract and ovarian tissue in young female calves. The significance of these morphology differences to advancing sexual maturation in heifers needs to be elucidate.